Forming and Co-simulation of Square and Triangular Waveforms by Using System Generator - Arserım, M.a.; Haydaroğlu, C.; Acar, H.; Uçar, A. (My University, 2019)
Nowadays Field Programmable Gate Arrays(FPGAs) are used to implement several processes in different areas such military defense, medical devices, automation, telecommunication, and image processing etc. Some of the advantages of FPGA are parallel and hardware processing. On the other hand programming FPGAs by classic design methodologies requires much effort. Therefore, design tools like System Generator can provide facilities about programming FPGAs. System Generator is a design tool from Xilinx to program the Xilinx FPGAs in MATLAB/Simulink graphic based editor. Also its block set is limited with respect to Simulink, has. In this study square, and triangular waveforms are built with the basic blocks of System Generator tool. These waveforms belong to basic sources for signal processing. Generally, they are used in power electronics especially for producing PWM, or sinus PWM. Also co-simulation can be done by using System Generator. Square waveform block, which is implemented, has variable amplitude, frequency, duty cycle, and offset values whereas triangular waveform has variable amplitude, frequency, and offset values. Triangular waveform has an error as 2 % due to data bus width.
Keywords: Mühendislik; Elektrik ve Elektronik; Bilgisayar Bilimleri; Yazılım Mühendisliği; Bilgisayar Bilimleri; Sibernitik; Bilgisayar Bilimleri; Bilgi Sistemleri; Bilgisayar Bilimleri; Donanım ve Mimari; Bilgisayar Bilimleri; Teori ve Metotlar; Bilgisayar Bilimleri; Yapay Zeka